Impact of Comorbidities on Prognosis and Treatment Outcomes in Elderly Patients with Hodgkin Lymphoma - Dávid Tóthfalusi; Boglárka Dobó; Fanni Borics; László Imre Pinczés; Árpád Illés; Zsófia Miltényi (Clinics and Practice)
Background/Objectives: Hodgkin lymphoma (HL) primarily affects young adults, but about 20% of cases occur in patients over the age of 60 years. Older individuals often have comorbidities and poorer functional status, which can affect treatment choices. Methods: We retrospectively analyzed data from HL patients over 60 years old who were treated at our institution between January 2010 and December 2023. We examined various factors, such as blood parameters (e.g., platelet count, lactate dehydrogenase (LDH), C-reactive protein (CRP)), PET/CT results and comorbidities (e.g., hypertension, diabetes, cardiovascular diseases), to assess their impact on overall survival (OS) and progression-free survival (PFS). Diagnostic efficiency was determined via receiver operating characteristic analysis, while the survival outcomes were evaluated using the Cox proportional hazards model. Results: A total of 35 patients with a median age of 68 were treated. The most common subtype was nodular sclerosis, and 72% of patients were in advanced stages at diagnosis. Treatment varied by age, with younger patients receiving ABVD and older patients (80–89) receiving brentuximab vedotin with dacarbazine. The survival of older patients, when analyzed by age groups, did not show a significant difference in the OS (p = 0.16) and PFS (p = 0.11). Comorbidities significantly worsened survival, with patients who scored > 7 on the Charlson Comorbidity Index (CCI) showing a 5-year PFS of 41.3%, compared to 91.3% for those who scored ≤ 7. Among the tested laboratory parameters, a platelet count over 310.5 G/L and an absolute lymphocyte count below 0.47 G/L were found to be independent risk factors for OS. Patients with neither or only one of these risk factors demonstrated a 5-year OS of 81.7%, whereas those presenting with both risk factors experienced a reduced 5-year OS of 70%. For PFS, a white blood cell count > 8.48 G/L, a platelet count > 310.5 G/L, and advanced age (>73.5 years) were identified as significant adverse prognostic factors. Patients with none of these risk factors had a 5-year PFS of 100%, whereas those with ≥ 1 risk factor had a 5-year PFS of 35.6%. Conclusions: Comorbidities play a greater role in prognosis than chronological age, emphasizing the need for personalized treatment approaches.